PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS TEKNOLOGI PADA MATA PELAJARAN IPA POKOK BAHASAN ORGAN TUBUH MANUSIA - Chiko Yuardan Yudas; Hendra Nelva Saputra; Zila Razilu (EDUTECH : Jurnal Inovasi Pendidikan Berbantuan Teknologi, 2026)
ABSTRACT This study was motivated by the suboptimal use of technology-based learning media in science education, particularly in teaching the topic of human body organs, which requires concrete visualization to facilitate students’ understanding. The study aimed to develop technology-based learning media for the topic of human body organs and to determine its feasibility and practicality based on evaluations from subject matter experts, media experts, and student responses. The research employed a Research and Development (R&D) method using the ADDIE model, which consists of the stages of analysis, design, development, implementation, and evaluation. The research subjects included three subject matter experts, three media experts, and fifteen fifth-grade students of SDN 7 Lasolo. The instruments used were subject matter expert validation sheets, media expert validation sheets, and student response questionnaires. Data were analyzed using quantitative and qualitative descriptive techniques through the calculation of mean scores and percentages. The results showed that the subject matter expert validation achieved a score of 82%, categorized as feasible, while the media expert validation achieved 86%, categorized as highly feasible. Student responses reached 89.56%, indicating that the media was highly practical. Based on these findings, the technology-based learning media on the topic of human body organs was deemed feasible and practical for use as an alternative science learning medium in elementary schools. ABSTRAK Penelitian ini dilatarbelakangi oleh belum optimalnya pemanfaatan media pembelajaran berbasis teknologi dalam pembelajaran IPA, khususnya pada materi organ tubuh manusia yang membutuhkan visualisasi konkret. Penelitian ini bertujuan mengembangkan media pembelajaran berbasis teknologi pada materi organ tubuh manusia serta mengetahui tingkat kelayakan dan kepraktisannya berdasarkan penilaian ahli materi, ahli media, dan respon siswa. Penelitian menggunakan metode penelitian dan pengembangan dengan model ADDIE yang meliputi tahap analisis, perancangan, pengembangan, implementasi, dan evaluasi. Subjek penelitian terdiri atas 3 ahli materi, 3 ahli media, dan 15 siswa kelas V SDN 7 Lasolo. Instrumen yang digunakan meliputi lembar validasi ahli materi, lembar validasi ahli media, dan angket respon siswa. Data dianalisis secara deskriptif kuantitatif dan kualitatif melalui perhitungan rata-rata skor dan persentase. Hasil penelitian menunjukkan bahwa validasi ahli materi memperoleh persentase 82% dengan kategori layak, validasi ahli media memperoleh persentase 86% dengan kategori sangat layak, dan respon siswa memperoleh persentase 89,56% dengan kategori sangat praktis. Berdasarkan hasil tersebut, media pembelajaran berbasis teknologi pada materi organ tubuh manusia dinyatakan layak dan praktis digunakan sebagai alternatif media pembelajaran IPA di sekolah dasar.